Two isostructural Ln-MOFs showing luminescent sensing (Eu) and slow magnetic relaxation (Dy) properties. Issue 44 (25th October 2018) - Yang, Chun; Zheng, Jie-Yu; Cai, Wen-Jing; Guo, Fu-Sheng; Wang, Yao-Yu
Abstract : Two isostructural lanthanide-based MOFs are reported. The Eu-MOF exhibiting luminescence properties can be utilized in ion detection and the Dy-MOF displays SMM behavior with an energy barrier (Δ U eff ) of 54 K. Abstract : Two isostructural lanthanide-based MOFs [Ln(HL)L]·H2 O (1-Ln, Ln = Eu, Dy, H2 L = 5-((pyridin-4-ylthio)methyl)isophthalic acid) were successfully obtained via the solvothermal reaction.1-Eu exhibits high fluorescence quenching efficiency for C2 O7 2− and Fe 3+, which can be potentially used as a luminescent probe;1-Dy behaves as a typical single-molecule magnet with an energy barrier (Δ U eff ) of 54(2) K.